Metabolic and Morphotypic Trade-Offs within the Eco-Evolutionary Dynamics of Escherichia coli - Nikola Zlatkov; Moa Elsa Cecilia Näsman; Bernt Eric Uhlin (Microbiology Spectrum, 2022)
ABSTRACT Escherichia coli arbitrarily encompasses facultative anaerobic, rod-shaped bacteria with defined respiratory and fermentative types of metabolism. The species diversification has been further advanced by atypical strains whose features deviate from the essential species-specific morphological and metabolic cutoff. The morphological cutoff is exemplified by bacterial filamentation. E. coli filamentation has been studied from two different perspectives: the first considers filamentation as a result of adaptive strategies and response to stress, while the second is based on findings from the cell division of E. coli’s conditional mutants. Another cutoff is represented by E. coli’s inability to use citrate as a sole carbon and energy source. In this study, we compared two atypical E. coli strains that belong to the same neuroinvasive ecovar but exhibit either of the two phenotypes that deviate from the species’ features. While E. coli RS218 exists in the form of filaments incapable of growth on citrate, strain IHE3034 is represented as normal-sized bacteria able to ferment citrate under oxic conditions in the presence of glucose; in this paper, we show that these two phenotypes result from a bona fide trade-off. With the help of comparative proteomics and metabolomics, we discovered the proteome required for the upkeep of these phenotypes. The metabolic profiles of both strains reveal that under aerobic conditions, RS218 undergoes oxidative metabolism, while IHE3034 undergoes anaerobic respiration. Finally, we show that the use of citrate and filament formation are both linked in a trade-off occurring via a c-di-GMP-dependent phase variation event. IMPORTANCE Aerobic use of citrate and filamentous growth are arbitrary cutoffs for the Escherichia coli species. The strains that exhibit them as stable phenotypes are called atypical. In this study, we compare two atypical neuroinvasive E. coli strains, which alternatively display either of these phenotypes. We present the proteome and metabolome required for the maintenance of filamentous growth and show that anaerobic nitrate respiration is the main requirement for the use of citrate. The fact that the two phenotypes are differentially expressed by each strain prompted us to check if they are part of a trade-off. Indeed, these atypical characters are reversible and result from a c-di-GMP phase variation event. Thus, we revealed hidden links between stable morphological and metabolic phenotypes and provided information about alternative evolutionary pathways for the survival of E. coli strains in various host niches.